Etika Bisnis: Sebuah Peran dalam Kemajuan Perusahaan - Rifyal Zuhdi Gultom; Yudi Rudi (Kafalah: Jurnal Ekonomi, Manajemen, dan Keuangan Syariah, 2026)
Business ethics is a concept that exists to apply ethical values in carrying out business activities. In terms of goals, not only profitable business is the main priority, but also business that is morally sound. This study aims to understand the concept of business ethics in general, both the goals and scope of business ethics, and how important it is in advancing a company. The research method used is a qualitative method with a library research approach. Literature study is a method that seeks references relevant to the problems identified. The application of business ethics in a company will also shape behavior that leads to optimal, productive, and more focused performance capabilities for the benefit of all stakeholders, thereby contributing to higher company performance..